The Knowledge, Skill, and Ability Requirements for Teamwork: Implications for Human Resource Management - Stevens, Michael J.; Campion, Michael A. (Journal of Management, 1994)
This study reviews the literature on groups to determine the knowledge, skill, and ability (KSA) requirements for teamwork. The focus is on: (1) KSAs rather than personality traits; (2) team rather than technical KSAs; and (3) the individual rather than team level of analysis. Fourteen specific KSAs are derived. Then, the implications of these teamwork KSAs for the modification or development of human resource (HR) management systems are determined, and research issues are discussed.